Variation in Response to Pharmacological Intervention with Risperidone and the Role of Adjuvant Medications in the Treatment of Autism Spectrum Disorders: A Systematic Review and Meta-analysis - Sharanabasayyaswamy Hiremath; Srinivas L. Devendrappa (Pharmacology and Clinical Pharmacy Research, 2022)
Non-genetic traits as predictors of variation in response to pharmacological interventions in ASD need to be identified for better management. This review aims to identify these non-genetic traits and the role of adjuvant medications in ASD. Electronic database searches in PUBMED and Cochrane libraries were conducted using MeSH search terms "Autism" and "Risperidone." Randomized or cross-over trials comparing the efficacy of ‘risperidone plus placebo’ vs. ‘risperidone plus adjuvant medications’ using Aberrant Behavior Checklist-Community Version (ABC-CV) scores in ASD patients of any age group were included in the analysis. The quantity of reduced irritability (ABC-I) sub-score was the primary outcome measure analyzed.In contrast, the reduction in remaining ABC-CV sub-scores at the end of 10 weeks were the secondary outcome measures analyzed. All the outcome measures were estimated by calculating the Mean Difference (MD) values and their 95% Confidence Intervals (CI) by both fixed and random effect models using Revman 5.4.1 software. A total of 13 trials were found to be eligible and included in the quantitative synthesis of efficacy. A small but significant decrease in the ABC irritability sub-score was evident in the ‘risperidone plus adjuvants’ group (MD: -3.19, 95% CI:-3.82, -2.56, N=658). The meta-analysis results attributed the highest decrease in ABC-irritability sub-scores to adjuvant topiramate. There is a possibility of bias and minimal impact of adjuvants in alleviating irritability symptoms of ASD. Baseline severity of irritability symptoms and the dose/medication regimen appear to be possible non-genetic traits responsible for variation in response to pharmacological intervention.